Comparison Analisys of Financial Performance of Village Owned Business Entity (BUMDes) “Bina Mandiri” Jada Bahrin Village and Village Owned Business Entity (BUMDes) “Pagarwan” Pagarawan Village 2019-2021 Period - Wahyuni, Wahyuni; Nugroho, Ari Agung; Hamsani, Hamsani (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
This study aims to analyze and compare the financial performance of BUMDes "Bina Mandiri" Jada Bahrin Village and BUMDes "Pagarawan" Pagarawan Village. The method used in this study is the quantitative method with a measuring instrument that uses ratio analysis and the CAMEL method. The rapid development of BUMDes in recent years has prompted the author to conduct research on Comparative Analysis of the Financial Performance of Village Owned Enterprises (BUMDes) "Bina Mandiri" Jada Bahrin Village and Village Owned Enterprises (BUMDes) "Pagarawan" Pagarawan Village for the 2019-2021 Period . The types and sources of data used are secondary data taken from the financial statements of BUMDes "Bina Mandiri" and BUMDes "Pagarawan" for the last 3 years (period 2019 to 2021). Data collection techniques used with documentation and literature review. Based on the results of the activity ratio research, it shows that BUMDes "Pagarawan" has better financial performance than BUMDes "Bina Mandiri", based on the profitability ratio shows that BUMDes "Bina Mandiri" has better financial performance than BUMDes "Pagarawan", while based on the analytical method CAMEL BUMDes “Bina Mandiri” has better financial performance than BUMDes “Pagarawan”. From the results of research for BUMDes "Bina Mandiri" and BUMDes "Pagarawan" in order to improve financial performance, especially in the activity ratio which is still in the bad category. Keywords: BUMDes, Financial Ratio, Financial Performance and Analisys CAMEL.